Kamus unggah-ungguh basa Jawa / R. Haryana Harjawiyana, Th. Supriya ; editor, I. Praptomo Baryadi - R. HARYANA HARJAWIYANA; Supriya, Th.; Praptomo Baryadi, I. (Kanisius, 2011)
ix, 192 hlm. : ilus. ; 24 cm [3 eks.]